Experimenter Presence or Absence: An Experimental Analogue with Implications for Organizational Behavior Management. Issue 4 (2nd October 2018) - Palmer, Michael G.; Johnson, C. Merle; Davis, Brian
ABSTRACT: Students performed a simulated bank-proofing task individually in a lab with either the experimenter present or absent. Although run rates were similar, those in the Experimenter-Absent Group were off-task twice as much during sessions. Error frequencies for both groups were low and similar while rates of responding were significantly higher (+13%) in the Experimenter-Present Group because participants were off-task less often. Most human lab experiments fail to specify whether experimenters are present or absent in the room and this extraneous variable is a potential confound that should be controlled in future studies.